Month that changed the world : July 1914 - Martel, Gordon (ACLS Humanities E-Book (Series), 2014)
Dedicating a chapter to every day of July 1914, the author retraces the actions that led to World War I, beginning with the assassination of Archduke Franz Ferdinand and following leaders of the time as they escalated the crisis.